A new species of the genus Ceraphron Jurine (Hymenoptera: Ceraphronidae) from India - Ghosh, Amit Kumar; Kumar, Vikas; Rameshkumar, Anandhan; Tyagi, Kaomud (Zootaxa, 2024)
Ceraphron initium sp. nov. is described and illustrated from Nagaland state of India based on male specimens. The genitalia of this new species is studied and compared with the closely related species C. semira Salden & Peters and C. thompsoni (Dalla Torre).